CALYPSO MUSIC: A POPULAR CULTURE FOR ESTABLISHING THE SENSE OF IDENTITY AND RESISTANCE - Djamila Mehdaoui; Yassmine Boukhalkhal; Fewzia Benyelles Bedjaoui (International Journal of Innovative Technologies in Social Science, 2025)
Calypso music emerges as a significant cultural feature and sign revealing the socio–historical continuum between Africa and the New World, since this musical genre is mutually and inextrably interconnected with the plantation fields and the many enslaved Africans. And because the African diaspora in the New World has been rigid and more enduring, suffering gives birth to myriads of artistic expressions and oral forms burgeoning from the inherently brutal treatment of planters, such as religious songs, folktales, and ritual practices. Therefore, Calypso appears as a unique mingling of dance and music expressing the African sensibility in terms of orality. Calypsonians, thus, continue in their imaginatively inventive tools and ways of artistic resistance to the diverse images of oppression and exploitation. On the other side, because of the privileged position it occupies in the Caribbean society, Calypso acts as a distinctive expression of collective identity. Therefore, this paper examines the relationship between the traumatic history and Calypso as a folkloric culture, and explores how this popular culture emerges as a site of negotiating identity and power relations. It concludes that Calypso and carnivals, as positive responses to the colonial hostilities, have continued to play major roles in establishing collective behaviors, maintaining the sense of identity, and emphasizing resistance through performance styles to preserve the bonds of their cultural heritage.